Biotech rice: Current developments and future detection challenges in food and feed chain. (June 2016) - Fraiture, Marie-Alice; Roosens, Nancy H.C.; Taverniers, Isabel; De Loose, Marc; Deforce, Dieter; Herman, Philippe
Abstract: Background: To improve agricultural practices and the food/feed security, plant breeding techniques were developed, including transgenesis commonly using Agrobacterium tumefaciens or biolistic technologies. To guarantee the traceability of GMO in food/feed chain and the consumer's freedom of choice, regulatory frameworks were established in many countries around the world, such as in Europe. Their implementations, including detection systems usually based on qPCR, are becoming complex and expensive regarding the number of analysis to perform. Moreover, the dispersion of publicly available information about developed GMO prevents to accurately estimate the efficiency of the standard detection system applied to unauthorized GMO. Scope and approach: To illustrate this problem, the case of rice, one of the leading staple crops, was investigated. An overview of worldwide developed biotech rice generated by transgenesis was thus conducted, based on 1067 peer-reviewed publications, and analysed regarding inter alia their expressed genes of interest and the corresponding traits, their transformation processes and the elements composing their transgenic cassettes. From this work, the power and weakness of the standard detection system, notably used by the European enforcement laboratories, are evaluated. To strengthen this system, especially with unauthorized GMO, additional strategies are suggested. Moreover, given the growing interest for biotech rice produced by new plant breeding techniques, related challenges for their detection are discussed. Key findings and conclusions: According to all collected information, suitable detection strategies, combining qPCR to additional technologies (e.g., DNA walking and NGS), are proposed to cover most of inventoried biotech rice. The present approach, including the data centralization to subsequently suggest appropriated detection strategies, can be extended to biotech events from different species. Highlights: Technical issues to detect unauthorized GMO are here illustrated with biotech rice. An overview of worldwide developed biotech rice is presented. Their detection in routine GMO analysis is discussed. Suitable detection strategies are suggested to target most of these biotech rice. The present approach can also be applied to biotech "non-rice" events.